2020
DOI: 10.1007/s10072-020-04521-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related strokes in adults below 55 years of age: a case series

Abstract: Background Coronavirus infection is a novel respiratory disease affecting people across the world. Although the majority of patients present with fever, dyspnea, cough, or myalgia, various signs and symptoms have been reported for this disease. Recently, neurological symptoms have been noticed in patients with COVID-19 with unknown etiology. However, the occurrence of strokes in young and middle aged patients with COVID-19 is not fully explained. Methods In this series, six patients younger than 55 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 16 publications
1
53
1
8
Order By: Relevance
“…Five younger (< 50 years old) patients presented with large-vessel stroke within a 2-week period at a New York City hospital, where historically an average of only 0.73 patients under 50 were treated for the condition during the same time frame over the previous 12 months (Oxley et al 2020). A similar case series, describing six patients with stroke under the age of 55, was recently reported from Iran (Ashrafi et al 2020).…”
mentioning
confidence: 78%
“…Five younger (< 50 years old) patients presented with large-vessel stroke within a 2-week period at a New York City hospital, where historically an average of only 0.73 patients under 50 were treated for the condition during the same time frame over the previous 12 months (Oxley et al 2020). A similar case series, describing six patients with stroke under the age of 55, was recently reported from Iran (Ashrafi et al 2020).…”
mentioning
confidence: 78%
“… 30 To our knowledge, several meta-analyses have investigated the association of cerebrovascular disease with the adverse outcomes in COVID-19 patients, 5 , 31 , 32 however, the data were uniformly estimated based on unadjusted effect estimates. As reported in previous studies, age, gender and pre-existing disease conditions could affected disease progression of COVID-19, 7 , 8 , 9 , 10 and might modulate the association between cerebrovascular disease and the adverse outcomes in COVID-19 patients. Therefore, it is an urgent need to verify this association by performing a quantitative meta-analysis based on adjusted effect estimates.…”
Section: Discussionmentioning
confidence: 59%
“…This suggested that the association between cerebrovascular disease and adverse outcomes in COVID-19 patients might be affected by many confounders such as age, gender, and other comorbidities. 7 , 8 , 9 , 10 Therefore, this meta-analysis was performed to evaluate the association between cerebrovascular disease and adverse outcomes in COVID-19 patients on the basis of adjusted effect estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Farzad et al reported a series of six patients younger than 55 years of age affected with COVID-19 and diagnosed with stroke. Brain CT scan findings of the patients revealed right middle cerebral artery (MCA) infarction (n = 3), left MCA (n = 2) and left basal ganglia infarction (n = 1), and the majority of the patients had large vessel stroke [42].…”
Section: Neurological Manifestations Of Sars-cov-2mentioning
confidence: 99%